Effects of liver-stage clearance by Primaquine on gametocyte carriage of Plasmodium vivax and P. falciparum - Wampfler, Rahel (PLoS Negl Trop Dis, 2017)
BACKGROUND: Primaquine (PQ) is the only currently licensed antimalarial that prevents Plasmodium vivax (Pv) relapses. It also clears mature P. falciparum (Pf) gametocytes, thereby reducing post-treatment transmission. Randomized PQ treatment in a treatment-to-reinfection cohort in Papua New Guinean children permitted the study of Pv and Pf gametocyte carriage after radical cure and to investigate the contribution of Pv relapses. METHODS: Children received radical cure with Chloroquine, Artemether-Lumefantrine plus either PQ or placebo. Blood samples were subsequently collected in 2-to 4-weekly intervals over 8 months. Gametocytes were detected by quantitative reverse transcription-PCR targeting pvs25 and pfs25. RESULTS: PQ treatment reduced the incidence of Pv gametocytes by 73%, which was comparable to the effect of PQ on incidence of blood-stage infections. 92% of Pv and 79% of Pf gametocyte-positive infections were asymptomatic. Pv and to a lesser extent Pf gametocyte positivity and density were associated with high blood-stage parasite densities. Multivariate analysis revealed that the odds of gametocytes were significantly reduced in mixed-species infections compared to single-species infections for both species (OR(Pv) = 0.39 [95% CI 0.25–0.62], OR(Pf) = 0.33 [95% CI 0.18–0.60], p<0.001). No difference between the PQ and placebo treatment arms was observed in density of Pv gametocytes or in the proportion of Pv infections that carried gametocytes. First infections after blood-stage and placebo treatment, likely caused by a relapsing hypnozoite, were equally likely to carry gametocytes than first infections after PQ treatment, likely caused by an infective mosquito bite. CONCLUSION: Pv relapses and new infections are associated with similar levels of gametocytaemia. Relapses thus contribute considerably to the Pv reservoir highlighting the importance of effective anti-hypnozoite treatment for efficient control of Pv. TRIAL REGISTRATION: ClinicalTrials.gov NCT02143934